Tetramethyl bisphenol F exposure induces human ovarian granulosa cell senescence and mouse ovarian damage by regulating ESRRB signalling - Huiyu Fan; Chunming Li; Yifei Lv; Tongyun Qi; Yizhou Huang; Linjuan Ma; Yibing Lan; Peiqiong Chen; Zheng Lou; Jianhong Zhou (Ecotoxicology and Environmental Safety)
Tetramethyl bisphenol F (TMBPF), regarded as a promising alternative to bisphenol A (BPA) across multiple industries, is now incorporated into polymer coatings for metal cans used in food and beverage packaging. Recent research has highlighted possible health risks associated with TMBPF, yet its impact on ovarian function and the mechanisms involved remain inadequately understood. This study provides a thorough evaluation of TMBPF's effects on granulosa cells (GCs) and uncovers its transgenerational influence on female reproductive health. We exposed pregnant CD1 mice to TMBPF at doses of 50 μg/kg/day or 200 μg/kg/day from gestational day 7 (GD7) through postnatal day 21 (PND21). Our findings indicated that maternal exposure to TMBPF adversely affects the reproductive system of the F1 generation by elevating the levels of E2, FSH, and LH, reducing the ovarian index, and increasing the number of collagen fibers in the ovarian stroma. The human granulosa-like tumor cell line KGN was employed as an experimental model to assess the toxic effects of TMBPF on GCs. The findings revealed that sublethal concentrations of TMBPF induced mitochondrial dysfunction, cellular senescence, and disrupted redox homeostasis in GCs in vitro. Our transcriptome sequencing analyses indicated that ESRRB upregulation might play a critical role in TMBPF-induced cellular senescence. Additionally, TMBPF exposure induced KGN cells senescence and senescent cell accumulation in F1 mouse ovaries by promoting ESRRB/p21 signalling. Collectively, our results indicate that TMBPF disrupts hormone levels in the ovaries, accelerates GCs senescence and promotes ovarian fibrosis, adversely affecting ovarian function in offspring. This study provides new insights into the potential effects of TMBPF exposure on the reproductive system and the related mechanisms.